2018
DOI: 10.1080/09168451.2017.1387515
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of nobiletin and epicatechin gallate on fructose uptake in human intestinal epithelial Caco-2 cells

Abstract: Inhibition of excessive fructose intake in the small intestine could alleviate fructose-induced diseases such as hypertension and non-alcoholic fatty liver disease. We examined the effect of phytochemicals on fructose uptake using human intestinal epithelial-like Caco-2 cells which express the fructose transporter, GLUT5. Among 35 phytochemicals tested, five, including nobiletin and epicatechin gallate (ECg), markedly inhibited fructose uptake. Nobiletin and ECg also inhibited the uptake of glucose but not of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Furthermore, authors demonstrated that epicatechin gallate suppressed fructose permeation in Caco-2 cells, suggesting that this compound suppressed the transepithelial transport of fructose across epithelial cell monolayers, in addition to its effect on fructose uptake. Lastly, authors reported that similar effects on fructose uptake and permeation were observed with nobiletin, another phytochemical tested in this study [107].…”
Section: Plant Extracts Inhibitors Of Fructose Transporterssupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, authors demonstrated that epicatechin gallate suppressed fructose permeation in Caco-2 cells, suggesting that this compound suppressed the transepithelial transport of fructose across epithelial cell monolayers, in addition to its effect on fructose uptake. Lastly, authors reported that similar effects on fructose uptake and permeation were observed with nobiletin, another phytochemical tested in this study [107].…”
Section: Plant Extracts Inhibitors Of Fructose Transporterssupporting
confidence: 82%
“…Likewise, Satsu et al demonstrated that epicatechin gallate inhibited fructose uptake in Caco-2 cells. Interestingly, this reduction in fructose uptake was not related to changes in the affinity (K m ) of GLUT5 for fructose, but with a decrease in the maximal velocity (V max ) [107]. Furthermore, authors demonstrated that epicatechin gallate suppressed fructose permeation in Caco-2 cells, suggesting that this compound suppressed the transepithelial transport of fructose across epithelial cell monolayers, in addition to its effect on fructose uptake.…”
Section: Plant Extracts Inhibitors Of Fructose Transportersmentioning
confidence: 98%
“…5,20 In addition, there is no report of EGCG inhibiting PEPT1 activity, whereas (-)-epicatechin gallate, another gallate catechin, not inhibiting the uptake transport of glycyl-sarcosine, a typical substrate of PEPT1, in Caco-2 cells. 21 This suggests that catechins may display only a weak inhibitory potential on PEPT activity. OATPs could also be candidate influx transporters, because EGCG and (-)-epicatechin gallate have been shown to inhibit OATP1A2, OATP1B1, and OATP2B1 activities in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Caco-2 cell line is a human colorectal adenocarcinoma line with no mucus present, used in LGS studies as a model of the intestinal epithelial barrier. As a result, the fructose uptake is reduced to the levels below 60% of the control [57]. An in vivo study on rats fed with fructose and dietary polyphenol-chrysinshowed alterations in GLUT-5 expression leading to its lower activity [55].…”
Section: Fructose As a More Affecting Factor Than Glucosementioning
confidence: 99%